Development of vocal emotion recognition in school-age children: The EmoHI test for hearing-impaired populations - Nagels, Leanne; Gaudrain, Etienne; Vickers, Deborah; Matos Lopes, Marta; Hendriks, Petra; Başkent, Deniz (PeerJ, 2020)
Traditionally, emotion recognition research has primarily used pictures and videos, while audio test materials are not always readily available or are not of good quality, which may be particularly important for studies with hearing-impaired listeners. Here we present a vocal emotion recognition test with pseudospeech productions from multiple speakers expressing three core emotions (happy, angry, and sad): the EmoHI test. The high sound quality recordings make the test suitable for use with populations of children and adults with normal or impaired hearing. Here we present normative data for vocal emotion recognition development in normal-hearing (NH) school-age children using the EmoHI test. Furthermore, we investigated cross-language effects by testing NH Dutch and English children, and the suitability of the EmoHI test for hearing-impaired populations, specifically for prelingually deaf Dutch children with cochlear implants (CIs). Our results show that NH children’s performance improved significantly with age from the youngest age group onwards (4–6 years: 48.9%, on average). However, NH children’s performance did not reach adult-like values (adults: 94.1%) even for the oldest age group tested (10–12 years: 81.1%). Additionally, the effect of age on NH children’s development did not differ across languages. All except one CI child performed at or above chance-level showing the suitability of the EmoHI test. In addition, seven out of 14 CI children performed within the NH age-appropriate range, and nine out of 14 CI children did so when performance was adjusted for hearing age, measured from their age at CI implantation. However, CI children showed great variability in their performance, ranging from ceiling (97.2%) to below chance-level performance (27.8%), which could not be explained by chronological age alone. The strong and consistent development in performance with age, the lack of significant differences across the tested languages for NH children, and the above-chance performance of most CI children affirm the usability and versatility of the EmoHI test.
Keywords: Emotion; Hearing loss; Cochlear implants; Cognitive development; Vocal emotion recognition; Auditory development; Hearing impairment; Perception